2020
DOI: 10.15275/cardioit.2020.0103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin/neprilysin inhibition on ventricular repolarization and clinical arrhythmogenesis

Abstract: Background: The most common reason for sudden cardiac death in heart failure is malign ventricular arrhythmias. LCZ 696 improves hospitalization and sudden cardiac death outcomes in heart failure, however mechanisms in preventing sudden cardiac death are still unknown. There is little information available assessing effect of LCZ 696 on Tp-e interval and related calculations. In this study, we aimed to investigate the impact of Sacubitril/valsartan therapy on Tp-e interval, Tp-e/QT ratio and Tp-e/QTc ratio in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The incidence of sudden cardiac death, ventricular arrhythmias and appropriate implantable cardioverter defibrillator (ICD) therapy was lower in HFrEF patients with sacubitril/valsartan compared to RAAS blockers [41][42][43][44]. In agreement, a 12-month "realworld" observational study of 167 patients with dilated cardiomyopathy due to ischemic and non-ischemic origins documented a markedly diminished incidence of ICD-detected atrial and ventricular arrhythmias following sacubitril/valsartan, together with a reduction in appropriate ICD shocks [45].…”
Section: The Effects Of Arni On Ventricular Arrhythmiasmentioning
confidence: 86%
“…The incidence of sudden cardiac death, ventricular arrhythmias and appropriate implantable cardioverter defibrillator (ICD) therapy was lower in HFrEF patients with sacubitril/valsartan compared to RAAS blockers [41][42][43][44]. In agreement, a 12-month "realworld" observational study of 167 patients with dilated cardiomyopathy due to ischemic and non-ischemic origins documented a markedly diminished incidence of ICD-detected atrial and ventricular arrhythmias following sacubitril/valsartan, together with a reduction in appropriate ICD shocks [45].…”
Section: The Effects Of Arni On Ventricular Arrhythmiasmentioning
confidence: 86%
“…As can be seen from Figure 1, sacubitril/valsartan reduces the occurrence of appropriate ICD shocks (95% confidence interval [CI] [1.57,4.67], Z = 3.57 [P < .001]). [8,[12][13][14] Similarly, a 6-minute walk test and echocardiographic evaluation of patients who underwent both ICD implantation and sacubitril/valsartan showed that even in ICD patients with a higher risk of arrhythmia, clinical, and functional improvements were significantly improved. [15] On the contrary, Vicent et al [16] report 6 cases of arrhythmic storm shortly after the initiation of sacubitril/valsartan, but the outcome is not enough to infer a cause-and-effect relationship between taking sacubitril/valsartan and arrhythmia due to the small sample size.…”
Section: What Was Found In Previous Researchmentioning
confidence: 99%
“…As can be seen from Figure 1 , sacubitril/valsartan reduces the occurrence of appropriate ICD shocks (95% confidence interval [CI] [1.57,4.67], Z = 3.57 [ P < .001]). [ 8 , 12 14 ] Similarly, a 6-minute walk test and echocardiographic evaluation of patients who underwent both ICD implantation and sacubitril/valsartan showed that even in ICD patients with a higher risk of arrhythmia, clinical, and functional improvements were significantly improved. [ 15 ]…”
Section: What Was Found In Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation